Sosialisasi Prosedur Pelaksanaan Program Magang MBKM Program Studi Pendidikan Olahraga Universitas Bina Darma - Sukmawati, Noviria; I Bagus Endrawan, I Bagus Endrawan; Melianty, Selvi; Kesumawati, Selvi Atesya (Abdibaraya, 2024)
Education is a communicating relationship involving the process of change, assessment, and skill from inside and outside the school. Education is one of the affairs that must be guaranteed and provided by the central government to local governments. The purpose of this service is to provide sports education study program students with an understanding of the procedures for implementing the internship program at the Merdeka Campus (MBKM) program. MBKM is not just a concept, but a journey that requires a joint commitment from the government, educational institutions, society, and the industrial sector. The Ministry of Education and Culture-Ristek has made an Independent Policy-Study Independent Campus, and one of the programs in the MBKM policy is the program. This program provides opportunities for students with what they get for one year or two semesters. One of the achievements of study program graduates is that students have the ability to solve problems in individual and group sports and through internship activities can train soft skills and hard skills that are mature and relevant to the needs of the times. The internship program can facilitate students to get learning and practice the skills gained during lectures to be applied to sports partners with the hope that this socialization can be useful for students to help government programs in sustainable development in the field of sports. Through the internship program, it is able to produce students who are ready with hard skills and soft skills obtained from the activities they participate in and the programs implemented can run optimally.